From the tetrarchs to the Theodosians : later Roman history and culture, 284-450 CE - McGill, Scott, 1968-; Sogno, Cristiana, 1969-; Watts, Edward Jay, 1975- (Cambridge, UK : Cambridge University Press, 2010)
'An integrated collection of essays examining the politics, social networks, law, historiography, and literature of the later Roman world. The volume treats three central themes: the first section looks at political and social developments across the period and argues that, in spite of the stress placed upon traditional social structures, many elements of Roman life remained only slightly changed. The second section focuses upon biographical texts and shows how late-antique authors adapted traditional modes of discourse to new conditions. The final section explores the first years of the reign of Theodosius I and shows how he built upon historical foundations while unfurling new methods for utilising, presenting, and commemorating imperial power. These papers analyse specific events and local developments to highlight examples of both change and continuity in the Roman world from 284-450.'--From publisher description.
Includes bibliographical references and index.
Keywords: Geschichte 284-450; Social change -- Rome -- History; Rome -- History -- Empire, 284-476.; Rome -- History -- Empire, 284-476 -- Historiography; Rome -- Politics and government -- 284-476.; Rome -- Civilization; Rome -- Social conditions